Prawne determinanty procesu kształcenia w szkołach wyższych w latach 1920–1990 (Część II) - Wojtczak, Krystyna (Wydawnictwo Naukowe UAM, 2014)
During the period under analysis, neither the doctrine, nor the available legal sources provided any help that would enable to differentiate between the concept of educating and teaching at schools of higher education. When referring to teaching, the legislator used the term with respect to the education provided to students, while when referring to the term education, the legislator would only adopt solutions conducive to the teaching. Apart from providing education and/or teaching, schools of higher education were also responsible for the upbringing of their students. This paper’s focus is on the meaning and extent of the triad of concepts: “educating-teaching-upbringing” based on the opinions presented in the doctrine and the legal regulations in force in Poland in the years 1920–1990. Understanding of each of these concepts constituted a starting point for further research and interpretation of the legal solutions adopted in order to identify the fundamental elements of the education process. Over the period 1920–1990, the legal status of schools of higher education was not uniform (there were state and non-state (private) ones, vocational or purely academic). The regime and management of those schools as well as the rights and duties of their staff and students also differed depending on the type of school. The academic staff was required to demonstrate high academic qualifi cations and exemplary morale, while students were expected to be creative and capable of understanding the content taught. Although it was the teachers and the students together who constituted the pillar of the education process, in order to achieve the didactic goals schools of higher had to satisfy certain conditions specifi ed by law, such as: properly selected faculty members, specifi ed rules of recruitment and enrolment, organisation of the teaching and development of relevant courses and syllabi for each year of study, and ascertainment of adequate conditions for their realisation (teaching infrastructure, fi nancing etc.) These requirements had to be met by both type of school: public and private likewise. Each reform in higher education (carried out in 1920, 1933, 1947, 1951, 1958 and 1982) brought about subsequent modifi cations of those requirements and obligations, which were implemented accordingly. Since schools of higher education were not immune to political and socio-economic changes, the reforms in education which they subsequently underwent included alternately centralistic and de-centralistic solutions.
Legal determinants of the education process in schools of higher education between 1920 and 1990 (Part II)
Keywords: schools of higher education in the Second Republic of Poland and in the Polish People’s Republic; teaching in schools of higher education; requirements needed to implement the education process